PENGARUH PENGETAHUAN DAN MODIFIKASI LINGKUNGAN RUMAH TERHADAP PENCEGAHAN PENULARAN COVID-19 DI KECAMATAN ENDE TENGAH KABUPATEN ENDE - Bedho, Marthina; Woga, Raimunda; Bai, Marieta K. S.; rifatunnisa (Poltekkes Kemenkes Kupang, 2023)
The Covid-19 virus is very easily transmitted, causing very high incidence of morbidity and mortality in the world since 2019. Covid-19 is a new virus that attacks the respiratory system, people are not fully familiar with it, so they still ignore health protocols causing transmission to continue to spread. It's good to prevent transmission starting at home, but with independent isolation at home, transmission of Covid-19 will easily occur from infected patients without symptoms to other family members. Central Ende District, where this research took place, there were 11 people in close contact, 42 people positive for the highest PCR SWAB in Ende Regency, 2 people in isolation at Ende Hospital, while 40 people are self-isolating at home. Family needs special attention in caring for self-isolation patients according to the 5 family tasks in the health sector, namely getting to know and modifying the home environment to prevent Covid-19 transmission. 19. Method. Design uses the Mix method with a cross sectional approach. The sample size is 40 patients in self-isolation at home using total sampling. Retrieval of data using questionnaires, and interviews. Bivariate Analysis: Chi-Square and Multivariate: Logistic Regression Test. Results: There is no influence of family knowledge of the Covid-19 problem on preventing Covid-19 transmission with a bivariate statistical test p-value 0.894 (p> 0.05). There is an effect of modifying the home environment of self-isolation patients on preventing Covid-19 transmission with the results of a bivariate statistical test p-value of 0.049. Conclusion: Modifying the home environment for self-isolation patients in preventing Covid-19 transmission is a health protocol that families must implement by including counseling family members by health center nurses